Determinants of Customer Loyalty Toward Islamic Financial Products: The Role of Perceived Value, Satisfaction, and Religious Commitment - Sadly, Effendi (PT Inovasi Pratama Internasional, 2025)
This study investigates the determinants of customer loyalty toward Islamic financial products, focusing on perceived value, customer satisfaction, and religious commitment. The Islamic finance sector has experienced significant growth, attracting customers seeking ethical financial solutions compliant with Sharia principles. Understanding the factors that drive customer loyalty is crucial for Islamic banks aiming to cultivate long-term relationships. Utilizing a quantitative approach, data were collected through surveys distributed to customers of Islamic banks. The findings reveal that both perceived value and customer satisfaction significantly influence customer loyalty, with perceived value leading to a stronger commitment among customers. Additionally, religious commitment was found to moderate the relationship between perceived value and loyalty, indicating that customers with higher religious commitment derive greater loyalty from their perceived value of Islamic financial products. These insights suggest that Islamic banks should enhance the perceived value of their offerings by highlighting both financial and spiritual benefits. Furthermore, improving customer satisfaction through high-quality service and responsiveness to client needs is essential for fostering loyalty. This study contributes to the understanding of customer behavior in the Islamic finance sector and provides practical implications for Islamic financial institutions seeking to strengthen customer loyalty. By aligning products with customer values and enhancing service quality, Islamic banks can effectively build and maintain lasting relationships with their clients, ultimately positioning themselves for sustained growth in a competitive market.